Tuning the Coherent Interaction of an Electron Qubit and a Nuclear Magnon - Noah Shofer; Leon Zaporski; Martin Hayhurst Appel; Santanu Manna; Saimon Covre da Silva; Alexander Ghorbal; Urs Haeusler; Armando Rastelli; Claire Le Gall; Michał Gawełczyk; Mete Atatüre; Dorian A. Gangloff (Physical Review X)
A central spin qubit interacting coherently with an ensemble of proximal spins can be used to engineer entangled collective states or a multiqubit register. Making full use of this many-body platform requires tuning the interaction between the central spin and its spin register. GaAs quantum dots offer a model realization of the central spin system where an electron qubit interacts with multiple ensembles of ∼10^{4} nuclear spins. In this work, we demonstrate tuning of the interaction between the electron qubit and the nuclear many-body system in a GaAs quantum dot. The homogeneity of the GaAs system allows us to perform high-precision and isotopically selective nuclear sideband spectroscopy, which reveals the single-nucleus electronic Knight field. Together with time-resolved spectroscopy of the nuclear field, this fully characterizes the electron-nuclear interaction for a priori control. An algorithmic feedback sequence selects the nuclear polarization precisely, which adjusts the electron-nuclear exchange interaction in situ via the electronic g-factor anisotropy. This allows us to tune directly the activation rate of a collective nuclear excitation (magnon) and the coherence time of the electron qubit. Our method is applicable to similar central-spin systems and enables the programmable tuning of coherent interactions in the many-body regime.